Trajectory Tracking Control of Mecanum Wheels Mobile Platform Based on MPC - Huang Xiaoyu; Sun Yongzhi; Li Jinrong; Wang Yiting; Yang Qiwei (Jixie chuandong)
For the trajectory tracking control problem of the omnidirectional mobile platform of Mecanum wheels, a strategy of double closed-loop control with model predictive control (MPC) and differential forward proportional plus integral plus derivative (PID) is proposed. The attitude control loop and velocity control loop are designed based on the kinematics characteristics of Mecanum wheels. The linear error model of the Mecanum wheels chassis is established by the attitude control loop, the quadratic objective function is designed, and the problem of path following is transformed into predictive control for the nonlinear model. In the velocity control loop, the differential forward PID controller is used to avoid the high-frequency disturbance to the system caused by frequent step changes of the input quantity, accelerate the convergence of the angular velocity of the Mecanum wheels, and enhance the stability of the system. Simulation experiments demonstrate that the controller designed in this study has better convergence speed and tracking accuracy than the commonly used trajectory algorithm, and it can provide good robustness to control the mobile platform of Mecanum wheels.